Preparation method and application of a lithium-sulfur battery positive electrode material rich in anion and cation defects
The precursor is generated through the hydrothermal reaction of cobalt acetate, zinc acetate and thiophene dicarboxylic acid, and a lithium-sulfur battery cathode material rich in anion and cation defects is formed during Joule heat treatment, which solves the problem of slow redox kinetics and slow oxidation-reduction kinetics of lithium-sulfur battery cathode materials. To solve the problem of capacity fading, efficient Li2S nucleation and dissolution is achieved, improving battery performance.
Patent Information
- Application Number
- CN202411264327.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing lithium-sulfur battery positive electrode materials have a slow redox kinetics and rapid capacity attenuation during charge and discharge cycles. The traditional preparation method consumes time and energy, and the accumulation of Li2S on the surface of the material leads to blockage of active sites.
Cobalt acetate, zinc acetate and thiophene dicarboxylic acid are hydrothermally reacted in deionized water to generate a precursor, which is then Joule heat treated with selenium powder in a Joule heat rapid heating device to form a lithium-sulfur battery cathode material rich in anion and cation defects.
By increasing the SE vacancy, provide more adsorption/activated sites, accelerate the LI2S nuclear, reduce the LI2S nuclear and dissolved diffusion energy and activation energy, promote li2S oxidation and restoration dynamics, improve the overall performance of lithium sulfur batteries, extend the extension of the lithium sulfur battery, extend the extended Capacity maintenance rate.
Smart Images

Figure CN118825267B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a lithium-sulfur battery positive electrode material rich in anion and cation defects, belonging to the technical field of lithium-sulfur battery positive electrode material preparation. Background Art
[0002] Lithium-sulfur batteries (LSBs) have become a research hotspot for potential energy storage devices due to their low cost, large specific capacity, and especially high theoretical energy density (close to 2800 Wh / kg). However, the commercialization of LSBs still faces several serious technical problems, the most important of which are slow redox kinetics and rapid capacity decay during charge and discharge cycles.
[0003] Transition metal selenides (TMSes) are considered to be one of the ideal materials for anchoring LiPSs and inhibiting the shuttle effect due to their high conductivity, strong polar surface, good thermal stability and catalytic activity. However, most of the research focuses on the composition, morphology and size regulation. Li2S tends to accumulate on the surface of the material, resulting in the blockage and inactivation of active sites. In particular, the research on existing cathode materials mainly focuses on accelerating the nucleation process of Li2S (Li2S4→Li2S), thereby promoting redox kinetics. In addition, the main preparation methods of existing TMSes are through calcination and solvothermal methods, which are time-consuming and energy-consuming. Therefore, it is of great significance to develop a simple method to prepare efficient lithium-sulfur battery cathode materials that can both stably nucleate and effectively dissociate Li2S to solve the above problems.
[0004] In view of the above shortcomings, an efficient and low-cost method is developed to prepare a high-efficiency lithium-sulfur battery positive electrode material that can both stably nucleate and effectively dissociate Li2S, thereby solving the problem of Li2S accumulated on the surface of the positive electrode material in the prior art causing the active sites to be blocked and deactivated. At present, no lithium-sulfur battery positive electrode material rich in anion and cation defects has been found.
[0005] The Chinese invention patent with publication number CN116960331A discloses a method for preparing a sulfurized polyacrylonitrile positive electrode material for lithium-sulfur batteries. The method is to react a variety of metal salts with organic ligands to obtain a precursor, then place the precursor in a tubular furnace for calcination, and then acid etch to obtain a target product, and finally the target product and sulfur powder are secondary calcined with polyacrylonitrile in a tubular furnace to obtain a positive electrode material. The preparation of this method is cumbersome, requiring not only secondary calcination but also acid treatment; the secondary calcination will increase energy consumption, and although the acid treatment will etch the material to obtain a wider pore range, the waste acid generated will cause environmental pollution. At the same time, the addition of polyacrylonitrile is to introduce more carbon sources and increase its conductivity, but this method does not require additional carbon sources. In addition, this method does not involve anion and cation defects (Co and Se).
[0006] The Chinese invention patent with publication number CN111434607A discloses a metal phosphide and heteroatom doped porous carbon composite material and its preparation and application. The method is to react a variety of metal salts with biomass-derived polymers containing oxygen, phosphorus, nitrogen or sulfur, and then carbonize them in a tubular furnace to obtain a metal phosphide and heteroatom doped porous carbon composite material. It can be seen from the nitrogen adsorption and desorption curve of the patent that the material belongs to the type I adsorption curve, indicating that it is a microporous material, not a multi-level porous structure material rich in mesopores and macropores; in addition, the use of traditional tubular furnace calcination method is prone to cause the collapse of the pore structure (smaller pore size) and metal atom agglomeration and the loss of defects (defect reduction), resulting in a decrease in electrochemical performance. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a positive electrode material for a lithium-sulfur battery rich in anion and cation defects, which can effectively increase the content of Se vacancies in the positive electrode material, provide more adsorption / active sites for polysulfides, accelerate the nucleation of Li2S, and promote the diffusion and catalysis of polysulfides / Li2S on the surface of the positive electrode material, reduce the diffusion energy barrier and activation energy of Li2S nucleation and dissolution, promote Li2S redox kinetics, improve the overall performance of the lithium-sulfur battery, and solve the problems of slow redox kinetics and rapid capacity decay during the discharge cycle.
[0008] To achieve this object, the technical solution of the present invention is:
[0009] A method for preparing a lithium-sulfur battery positive electrode material rich in anion and cation defects comprises the following steps:
[0010] (1) adding cobalt acetate, zinc acetate and thiophene dicarboxylic acid into deionized water, stirring and mixing to obtain a mixed solution, transferring the mixed solution to a closed state for hydrothermal reaction, centrifuging, washing and vacuum drying to obtain a precursor;
[0011] (2) Selenium powder and precursor are placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively, and then Joule heat treatment is performed under a nitrogen protective atmosphere to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects.
[0012] Furthermore, in step (1), the ratio of cobalt acetate, zinc acetate, thiophene dicarboxylic acid and deionized water in the mixed solution is: 1mmol:1.1-1.5mmol:2-4mmol:20-40ml.
[0013] Furthermore, in step (1), the hydrothermal reaction conditions are: reaction temperature 100-150° C., reaction time 5-10 h.
[0014] Furthermore, in step (1), the washing conditions are: washing with N,N-dimethylformamide, deionized water, and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 5-10 h.
[0015] Furthermore, in step (2), the ratio of the amount of selenium powder to the precursor is: 0.02-0.06g:0.01g.
[0016] Furthermore, in step (2), the conditions of the Joule heat treatment are: heat treatment temperature 350-1000°C, heating rate 1000-3000°C / s, and Joule heat treatment times 3-10 times. The Joule heat treatment is heating from room temperature to the target temperature and then naturally cooling to room temperature, which is represented as one time.
[0017] Another object of the present invention is to provide an application of a lithium-sulfur battery positive electrode material rich in anion and cation defects prepared by the above method, which is applied to a lithium-sulfur battery positive electrode.
[0018] The beneficial effects of the present invention are:
[0019] (1) Compared with the traditional calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high preparation efficiency and low energy consumption. The extreme environment caused by rapid heating gives the material a large number of defects, while extremely rapid cooling can largely retain these defects.
[0020] (2) The present invention forms a precursor containing sulfur by reacting cobalt and zinc metal ions with sulfur-containing carboxylic acid ligands. The precursor is subjected to a selenization reaction using Joule heat treatment technology, and zinc ions can be doped into the formed cobalt selenide lattice. Since the precursor is rich in sulfur, sulfur can inhibit the complete selenization of the metal, forming zinc ion-doped cobalt selenide rich in selenium vacancies, that is, a lithium-sulfur battery positive electrode material rich in anion and cation defects of Co and Se. Compared with the traditional method of manufacturing defects by long-term heating, multi-step calcination, and introduction of external fields such as magnetic fields and plasma fields, this method is more efficient and less costly; in addition, the positive electrode material prepared by this method is rich in anion and cation defects, which can significantly increase the charge accumulation of the catalytic center Co, so that it forms more chemical bonds with polysulfides, while weakening the Co-S bond energy and generating abundant lattice vacancies and active centers to promote the diffusion and catalysis of polysulfides / Li2S on the surface of the electrocatalyst, thereby reducing the diffusion energy barrier and activation energy of Li2S nucleation and dissolution, thereby promoting the redox kinetics of Li2S and effectively improving the overall performance of lithium-sulfur batteries.
[0021] (3) The lithium-sulfur battery positive electrode material rich in anion and cation defects prepared by the present invention has a pore size range of 4-60nm, and belongs to a multi-level pore structure of mesopores and macropores, and has outstanding application performance in the positive electrode of lithium-sulfur batteries. At a high rate of 2C, the initial specific capacity of the lithium-sulfur battery is as high as 680.36-799.60mAh / g, and the capacity retention rate after 500 cycles is 75.02-80.36%; at a high rate of 4C, the initial specific capacity is as high as 580.42-680.51mAh / g; the recovery rate when switching from 4C to 0.2C is 90.1-91.2%, indicating good high-rate capacity and reversibility. Therefore, it has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The electron paramagnetic resonance spectrum (EPR) of the lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1, Comparative Example 1 and Comparative Example 3;
[0023] Figure 2 This is a transmission electron microscope energy spectrum (TEM-Mapping) diagram of the lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1;
[0024] Figure 3 This is a test diagram of the electrochemical cycle performance of the lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1 at a 2C rate;
[0025] Figure 4 This is a high rate test diagram of the lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1 at 0.2-4C. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.
[0027] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.
[0028] In a specific embodiment of the present invention, the Joule heat rapid heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1
[0029] (1) 1 mmol of cobalt acetate, 1.3 mmol of zinc acetate, and 3 mmol of thiophene dicarboxylic acid were added to 30 mL of deionized water, and the mixture was stirred to obtain a mixed solution. The mixed solution was transferred to a reactor for hydrothermal reaction at a temperature of 130 ° C and a reaction time of 8 h. The mixture was centrifuged, washed four times with N, N-dimethylformamide, deionized water, and ethanol, respectively, and vacuum dried at 65 ° C for 8 h to obtain a precursor.
[0030] (2) 0.04 g of selenium powder and 0.01 g of precursor were placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, Joule heat treatment was performed 6 times under a nitrogen protective atmosphere. The Joule heat treatment temperature was 750°C and the Joule heat treatment heating rate was 2000°C / s to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects. Example 2
[0031] (1) 1 mmol of cobalt acetate, 1.1 mmol of zinc acetate, and 2 mmol of thiophene dicarboxylic acid were added to 20 mL of deionized water, and the mixture was stirred to obtain a mixed solution. The mixed solution was transferred to a reactor for hydrothermal reaction at a temperature of 150°C and a reaction time of 5 h. The mixture was centrifuged, washed three times with N,N-dimethylformamide, deionized water, and ethanol, respectively, and dried under vacuum at 50°C for 10 h to obtain a precursor.
[0032] (2) 0.02 g of selenium powder and 0.01 g of precursor were placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, Joule heat treatment was performed 10 times under a nitrogen protective atmosphere at a Joule heat treatment temperature of 350 °C and a Joule heat treatment heating rate of 1000 °C / s to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects. Example 3
[0033] (1) Add 1mmol of cobalt acetate, 1.5mmol of zinc acetate, and 4mmol of thiophene dicarboxylic acid to 40mL of deionized water, stir and mix well, and then transfer to a reactor for hydrothermal reaction. The reaction temperature is controlled at 100°C and the reaction time is 10h. The precursor is obtained by centrifugation, washing with N,N-dimethylformamide, deionized water, and ethanol five times respectively, and vacuum drying at 80°C for 5h.
[0034] (2) 0.06 g of selenium powder and 0.01 g of precursor were placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, Joule heat treatment was performed three times under a nitrogen protective atmosphere at a Joule heat treatment temperature of 1000 °C and a Joule heat treatment heating rate of 3000 °C / s to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects. Example 4
[0035] (1) 1 mmol of cobalt acetate, 1.2 mmol of zinc acetate, and 2.5 mmol of thiophene dicarboxylic acid were added to 25 mL of deionized water, stirred and mixed, and then transferred to a reactor for hydrothermal reaction. The reaction temperature was controlled at 120 °C and the reaction time was 8 h. The precursor was obtained by centrifugation, washing with N,N-dimethylformamide, deionized water, and ethanol four times, and vacuum drying at 75 °C for 6 h.
[0036] (2) 0.03 g of selenium powder and 0.01 g of precursor were placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, respectively. Then, Joule heat treatment was performed 6 times under a nitrogen protective atmosphere. The Joule heat treatment temperature was 850°C and the Joule heat treatment heating rate was 2000°C / s to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects. Comparative Example 1
[0037] The difference between Comparative Example 1 and Example 1 is that the heating device and heating conditions in step (2) are different, and the other conditions remain unchanged. The specific operation is as follows:
[0038] 0.01 g of the precursor was placed in the center of the temperature zone of the tubular furnace, and 0.04 g of sulfur powder was placed upstream of the tubular furnace. The mixture was calcined under a nitrogen protective atmosphere at a temperature of 750°C and a heating rate of 5°C / min. The reaction was kept warm for 2 hours to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects. Comparative Example 2
[0039] The difference between Comparative Example 2 and Example 1 is that zinc acetate is not added in step (1), and the other steps remain unchanged. Comparative Example 3
[0040] The difference between Comparative Example 3 and Example 1 lies in the presence or absence of a sulfur-containing organic ligand in step (1), the replacement of thiophene dicarboxylic acid with terephthalic acid, and the other aspects remaining unchanged.
[0041] Application Example 1
[0042] The lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1-4 and Comparative Example 1-3 was mixed with sublimated sulfur in a mass ratio of 1:3 and placed in a sealed container, and heated at 160° C. for 12 h to solidify sulfur to obtain a solidified positive electrode material.
[0043] The solid sulfur positive electrode material was used as the positive electrode of the lithium-sulfur battery, the polypropylene porous membrane (Celgard2300) was used as the separator, the lithium foil was used as the negative electrode, and the electrolyte (a mixed solution of 1 mol / L lithium bistrifluoromethanesulfonyl imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane was 1:1)) was assembled in a glove box full of inert atmosphere protection. The electrochemical cycle performance test was carried out at a 2C rate and a high rate test at 0.2-4C on the CT-4008-5A6V system. The test results are shown in Table 1.
[0044]
[0045] The pore size distribution test results of nitrogen full adsorption are the full pore size distribution results based on the NLDFT model at 77K.
[0046] As shown in Table 1, the use of tubular furnace calcination and Joule heat heating device will affect the defects and pore size of the material. The extreme environment of high temperature and high pressure caused by the rapid heating and heat preservation process of the Joule heat device is conducive to the formation and retention of defects and the formation of a multi-level pore structure. Therefore, Example 1 has better electrochemical performance than Comparative Example 1; the addition of zinc acetate will help to form zinc ion-doped cobalt selenide rich in selenium vacancies, that is, a lithium-sulfur battery positive electrode material rich in anion and cation defects; the addition of thiophene dicarboxylic acid without sulfur-containing organic ligands will lead to complete selenization of the metal, resulting in a lithium-sulfur battery positive electrode material rich in Co ion defects, and poor electrochemical performance. It can be seen that the addition of zinc acetate and sulfur-containing organic ligand thiophene dicarboxylic acid and the calcination treatment of the Joule heat heating device are key factors in the preparation method.
[0047] Figure 1 The electron paramagnetic resonance spectra (EPR) of the positive electrode materials of lithium-sulfur batteries rich in anion and cation defects obtained in Example 1, Comparative Example 1 and Comparative Example 3. It can be seen from the figure that an obvious EPR signal is presented at g = 2.0003, corresponding to the uncoordinated electrons captured by Se vacancies, wherein the Se vacancies in Example 1 are significantly denser, indicating that the S element in the ligand and the Joule heat treatment technology can significantly increase the Se vacancy density of the selenide product, provide more adsorption / active sites for LiPS, and accelerate the nucleation of Li2S.
[0048] Figure 2 This is a transmission electron microscope energy spectrum (TEM-Mapping) diagram of the lithium-sulfur battery positive electrode material rich in anion and cation defects obtained in Example 1. It can be seen from the figure that the two elements Zn and Co are evenly distributed, indicating that Zn replaces the position of Co and realizes Zn doping. Zn doping can optimize the electronic structure of Co and generate a local electric field, reduce the reaction energy barrier and accelerate the dissolution of Li2S.
[0049] Figure 3 The electrochemical performance test diagram of the positive electrode material of lithium-sulfur battery rich in anion and cation defects obtained in Example 1 at 2C rate. It can be seen from the figure that the positive electrode material shows a first-cycle discharge of 799.6mAh / g. After 500 cycles, the capacity is maintained at 642.6mAh / g, the average capacity decay rate per cycle is 0.0393%, and the capacity retention rate is 80.36%. Combined with the data in Table 1, compared with Example 1, Comparative Examples 1-3 show poor cycle stability and higher capacity decay rate under the same conditions. The main reasons for the excellent performance of Example 1 are as follows: Example 1 has abundant Se vacancies (Se defects) and Zn doping (Co defects), which have efficient bidirectional catalytic effects of stable nucleation and efficient dissociation of Li2S. Among them, Se vacancies (Se defects) provide more adsorption / active sites for LiPS and accelerate Li2S nucleation; while Zn doping (Co defects) can reduce the reaction energy barrier and accelerate Li2S dissolution. The synergistic effect induced by vacancy and heteroatom doping effectively suppresses the shuttle effect and increases the utilization of S, thereby improving the electrochemical performance (capacity and cycling stability).
[0050] Figure 4 The electrochemical performance diagram of the lithium-sulfur battery cathode material rich in anion and cation defects obtained in Example 1 at different rates. It can be seen from the figure that at a high charge and discharge rate of 4C, a specific capacity of 702.4 mAh / g can be achieved, showing good high-rate capacity; at the same time, at current densities of 0.2C, 0.5C, 1C, 2C, 3C, and 4C, 1110.2mAh / g, 1002.5mAh / g, 900.2mAh / g, 799.6mAh / g, 720.8mAh / g, and 680.5mAh / g were reached respectively, and then the capacity was restored to 1000.8mAh / g after switching to 0.2C at a current density of 4C, and the capacity recovery rate reached 90.1%, indicating that the lithium-sulfur battery cathode material rich in anion and cation defects has highly reversible electrochemical properties.
[0051] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a lithium-sulfur battery positive electrode material rich in anion and cation defects, characterized in that: The following steps are involved: (1) adding cobalt acetate, zinc acetate and thiophene dicarboxylic acid into deionized water, stirring and mixing to obtain a mixed solution, transferring the mixed solution to a closed state for hydrothermal reaction, centrifuging, washing and vacuum drying to obtain a precursor; (2) Selenium powder and precursor are placed on the left and right ends of the groove of the graphite sample stage of the Joule heat rapid heating device, and then Joule heat treatment is performed under a nitrogen protective atmosphere to obtain a lithium-sulfur battery positive electrode material rich in anion and cation defects; In the step (2), the conditions of the Joule heat treatment are: heat treatment temperature 350-1000°C, heating rate 1000-3000°C / s, and Joule heat treatment times 3-10 times; In the step (1), the ratio of cobalt acetate, zinc acetate, thiophene dicarboxylic acid and deionized water in the mixed solution is: 1mmol:1.1-1.5mmol:2-4mmol:20-40ml.
2. The method for preparing a lithium-sulfur battery positive electrode material rich in anion and cation defects according to claim 1, characterized in that: In the step (1), the hydrothermal reaction conditions are: reaction temperature 100-150° C., reaction time 5-10 h.
3. The method for preparing a lithium-sulfur battery positive electrode material rich in anion and cation defects according to claim 1, characterized in that: In the step (1), the washing conditions are: washing with N,N-dimethylformamide, deionized water, and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 5-10 hours.
4. The method for preparing a lithium-sulfur battery positive electrode material rich in anion and cation defects according to claim 1, characterized in that: In the step (2), the ratio of the amount of selenium powder to the amount of the precursor is 0.02-0.06 g:0.01 g.
5. An application of a lithium-sulfur battery positive electrode material rich in anion and cation defects prepared by the preparation method according to any one of claims 1 to 4, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.
Citation Information
Patent Citations
Metal phosphide and heteroatom doped porous carbon composite material as well as preparation and application thereof
CN111434607A
Preparation method of sulfurized polyacrylonitrile positive electrode material for lithium-sulfur battery
CN116960331A
Method for rapidly preparing cobalt selenide@nitrogen-doped carbon composite electrode material
CN113772652A
Preparation method and application of nitrogen-doped porous carbon coated cobalt diselenide composite material
CN114229805A